Supercritical fluid extraction (SFE) – a green process of extracting bioactive compounds from Zingiberaceae plants - Omar, Muhammad Nor; Hasali, Nor Hazwani; Razman, Summaiya; Zuberdi, Ahmad Muzammil (2013)
Introduction: The supercritical fluid extraction (SFE) is a technology of interest to the food, cosmetics and pharmaceuticals industries, as an alternative to conventional methods, i.e. solvent extraction and solid-phase microextraction (SPME). SFE employs the use of supercritical fluid as the extracting solvent replacing the use of conventional organic solvents. Materials and Methods: The essential oils of Zingiber puberulum, Zingiber spectabile and Kaempferia galanga were extracted using SFE at 48 Mpa and 40°C of extracting pressure and temperature respectively. The oils were then analysed using gas chromatography-mass spectrometry (GC-MS) instrument. Results: Twenty-one compounds were found in the SFE extract of Z. puberulum with fatty acids; i.e. palmitic acid (65.7%) and oleic acid (15.9%) were the major constituents and small percentages of various terpenic compounds. The sesquiterpene compounds identified in the SFE extract of Z. puberulum were α-bisabolol, β-elemene and caryophyllene while in Kaempferia galanga, the major compound extracted was ethyl p-methoxycinnamate. Conclusion: It was found that the bioactive molecules in Zingiber family could be successfully extracted using SFE by optimizing the extracting conditions in order to ensure the optimum yield of the bioactive compounds.